Mechanism of aortic root dilation and cardiovascular function in tetralogy of Fallot. Issue 5 (13th May 2016) - Seki, Mitsuru; Kuwata, Seiko; Kurishima, Clara; Nakagawa, Ryo; Inuzuka, Ryo; Sugimoto, Masaya; Saiki, Hirofumi; Iwamoto, Yoichi; Ishido, Hirotaka; Masutani, Satoshi; Senzaki, Hideaki
Abstract: The aortic root dilation in tetralogy of Fallot (TOF) is a long‐term clinical problem, because a severely dilated aorta can lead to aortic regurgitation, dissection, or rupture, which can be fatal, necessitating surgical intervention. The details of the mechanism of aortic root dilation, however, are unclear. We have shown that aortic stiffness is increased in patients with repaired TOF, and may mirror the histological abnormality of elastic fiber disruption and matrix expansion. This aortic stiffness is related closely to the aortic dilation, indicating that aortic stiffness may be a predictor of outcome of aortic dilation. Furthermore, the aortic volume overload is a very important determinant of aortic diameter in TOF patients before corrective surgery. In addition, a chromosomal abnormality and the transforming growth factor‐β signaling pathway, a major contributor to aortic dilation in Marfan syndrome, also affect this mechanism. In this way, aortic dilation in TOF patients is suggested to be a multifactorial disorder. The aim of this review was therefore to clarify the mechanism of aortic dilation in TOF, focusing on recent research findings. Studies linking histopathology, mechanical properties, molecular/cellular physiology, and clinical manifestations of aortic dilation facilitate appropriate treatment intervention and improvement of long‐term prognosis of TOF.